Learning to read across languages and writing systems - Verhoeven, Ludo Th.; Perfetti, Charles A. (Cambridge, United Kingdom Cambridge University Press, 2017)
"Around the world, children embark on learning to read in their home language or writing system. But does their specific language, and how it is written, make a difference to how they learn? How is learning to read English similar to or different from learning in other languages? Is reading alphabetic writing a different challenge from reading syllabic or logographic writing? Learning to Read across Languages and Writing Systems examines these questions across seventeen languages representing the world's different major writing systems. Each chapter highlights the key features of a specific language, exploring research on learning to read, spell, and comprehend it, and on implications for education. The editors' introduction describes the global spread of reading and provides a theoretical framework, including operating principles for learning to read. The editors' final chapter draws conclusions about cross-linguistic universal trends, and the challenges posed by specific languages and writing systems"--Provided by publisher.
"The Chinese script is one of the oldest in the world. In fact, among the few scripts in use before 1000 BC, Chinese is the only one still used (Taylor & Taylor, 1995). The earliest Chinese characters were pictograms, however over time Chinese evolved into a logographic script (DeFrancis, 1984). Today, there is considerable diversity both in the Chinese script itself, and in reading instruction across the different Chinese-speaking societies. The Chinese government simplified 2,238 commonly used characters in 1964 . Simplified characters are now used in Mainland China and Singapore, whereas traditional characters have been kept in Hong Kong and Taiwan. Although most Chinese children receive reading instruction only in simplified or traditional characters, it seems relatively easy for an educated person to read the other form. However, simplification is highly controversial, because characters not only represent a writing system but also embody a 5000-year old culture and tradition. Pinyin is used as an auxiliary alphabet in Mainland China to denote character pronunciation. Pinyin consists of the 26 letters of the Roman alphabet plus u and is completely transparent in letter-sound correspondences. Zhuyinfuhao (phonetic symbols), a phonetic system made up of ancient characters and character components, is used in Taiwan. No transliteration systems are used in Hong Kong. 1.3. Literacy and schooling"--Provided by publisher.
1. Introduction: universals in learning to read across languages and writing systems Ludo Verhoeven and Charles Perfetti -- 2. Learning to read Chinese Becky Chen-Baumgarten and Adrian Pasquarella -- 3. Learning to read Japanese Keiko Koda -- 4. Learning to read Korean Min Wang, Jeung-Ryeul Cho and Chuchu Li -- 5. Learning to read Kannada Sonali Nag -- 6. Learning to read Arabic Elinor Saiegh-Haddad -- 7. Learning to read Hebrew David Share -- 8. Learning to read Greek Athanassios Protopapas -- 9. Learning to read Italian Christina Burani, Anna Thornton and Pierluigi Zoccolitti -- 10. Learning to read French Helene Deacon, Alain Desrochers and Kyle Levesque -- 11. Learning to read Spanish Sylvia Defior and Fransisca Serrano -- 12. Learning to read German Karin Landerl -- 13. Learning to read Dutch Ludo Verhoeven -- 14. Learning to read English Charles Perfetti -- 15. Learning to read Czech and Slovakian Marketa Caravolas -- 16. Learning to read Russian Elena Grigorenko, Sergey Kornilov and Natalia Rakhlin -- 17. Learning to read Finnish Mikko Aro -- 18. Learning to read Turkish Aydin Durgunoglu -- 19. Epilogue: universals and particulars in learning to read across seventeen orthographies Charleprs Perfetti and Ludo Verhoeven.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching -- Foreign speakers; Comprehension; Reading; Reading -- Social aspects; Written communication -- Social aspects; Reading comprehension -- Study and teaching -- Cross-cultural studies; Linguistic universals